Echocardiographic improvement of left atrial booster pump and reservoir function observed in heart failure with improved ejection fraction and its prognostication - Hwei Sung, Ling; en ze, Chan; Han Bing, Chow (Elsevier, 2023)
Introduction The novel subgroup of Heart Failure with improved ejection fraction(HFimpEF) is focused on improving left ventricle systolic function, but there is sparse data on left atrial(LA) recovery. Recent studies observed reversal remodelling of LA echocardiographic volume indices in HFimpEF. However, there is a lack of data on the echocardiographic description of volumetric LA functions, such as booster pump and reservoir dysfunction, in patients with HFimpEF. Objectives 1To describe the changes in echocardiographic volumetric indexes of LA function, such as changes in LA reservoir function, LA conduit function, LA booster pump and LA sphericity index in a patient with HFimpEF. 2To examine the correlation of these volumetric indexes with NT-ProBNP, 1-year composite mortality or heart failure (HF) events outcome. Method This observational study in Sarawak Heart Center, HF clinic, involves 53 consecutive patients with HFimpEF. Clinical records, echocardiographic data and 1-year composite clinical outcomes were analyzed retrospectively. Results The mean age is 52 ± 14 years; 81% were male, and 73% were non-ischemic in aetiology. All 53 were NYHA class I/II. 75.5% had hypertension, and 45.3% had diabetes. 17% had atrial fibrillation(AF). The median index left ventricle ejection fraction (LVEF), and NT-ProBNP were 54.4(44.1-61.1)% and 109.7(34.5-444.1)pg/ml. The median LA Volume indexed by body surface area(LAVI) of the initial echocardiography was 33.9(26.2-45.6) mL/m2, of which 49.1% were enlarged (LAVI >34 ml/m2), while the median Conclusion In our study cohort, HFimpEF is followed by favourable LA reverse remodelling. More study is needed to explore the prognostic significance of this finding among HFimpEF patients.